Distinct mast cell subpopulations within and around lymphatic vessels regulate lymph flow and progression of inflammatory-erosive arthritis in TNF-transgenic mice - Peng, Yue; Kenney, H. Mark; de Mesy Bentley, Karen L.; Xing, Lianping; Ritchlin, Christopher T.; Schwarz, Edward M. (Frontiers in Immunology, 2023)
Objective. Inflammatory-erosive arthritis is exacerbated by dysfunction of joint-draining popliteal lymphatic vessels (PLVs). Synovial mast cells are known to be pro-inflammatory in rheumatoid arthritis (RA). In other settings they have anti-inflammatory and tissue reparative effects. Herein, we elucidate the role of mast cells on PLV function and inflammatory-erosive arthritis in tumor necrosis factor transgenic (TNF-tg) mice that exhibit defects in PLVs commensurate with disease progression.Methods. Whole mount immunofluorescent microscopy, toluidine blue stained histology, scanning electron microscopy, and in silico bioinformatics were performed to phenotype and quantify PLV mast cells. Ankle bone volumes were assessed by μCT, while corresponding histology quantified synovitis and osteoclasts. Near-infrared indocyanine green imaging measured lymphatic clearance as an outcome of PLV draining function. Effects of genetic MC depletion were assessed via comparison of 4.5-month-old WT, TNF-tg, MC deficient Kit W-sh/W- sh (cKit -/-), and TNF-tg x cKit -/-mice. Pharmacological inhibition of mast cells was assessed by treating TNF-tg mice with placebo or cromolyn sodium (3.15mg/kg/day) for 3-weeks.Results. PLVs are surrounded by MCT + /MCPT1 + /MCPT4 + mast cells whose numbers are increased 2.8-fold in TNF-tg mice. The percentage of peri-vascular degranulating mast cells was inversely correlated with ICG clearance. A population of MCT + /MCPT1 -/MCPT4 -mast cells were embedded within the PLV structure. In silico single-cell RNA-seq (scRNAseq) analyses